Life threatening airway obstruction: a hazard of concealed eating disorders. Issue 5 (September 1998) - Jones, T M; Luke, L C
Abstract : The ingestion of unusual objects is not uncommon in florid mental illness. Less common is the accidental ingestion of a foreign body which has been used to induce vomiting. A case is reported of complete dysphagia that resulted from impaction of a plastic fork in the hypopharynx. The patient had been attempting to induce vomiting and, as a result of the presentation, was found to be suffering from a previously concealed eating disorder (bulimia). Self induced vomiting is one criterion for the diagnosis of bulimia and a review of the literature indicates that accidental ingestion of large foreign bodies is an increasingly familiar hazard of occult bulimia.